Analisa Manajemen Risiko Pada Aplikasi E-Smart Di BKPSDM Lombok Tengah Menggunakan ISO 31000 - Wahyuni Putri, Sri; Ashari, Maulana; Mardi, Mardi; Fadli, Sofiansyah (Universitas Pahlawan Tuanku Tambusai, 2024)
To make it easier to record daily activities at the BKPSDM (Agency for Personnel and Human Resources Development) Central Lombok district, the E-Smart application has been implemented, which is a website-based application used by all ASN (State Civil Apparatus) consisting of PNS. This application allows for threats and attacks that pose risks, which can disrupt the process of using the application. Therefore, this article aims to identify the risks in E-Smart application that focuses on the ISO 31000 Method.ISO 31000 is a framework published by the International Organization for Standardization which contains guidelines for implementing risk management.Based on this research, there are 4 possible risks that fall into the High Level of Risk, namely Misuse of Access Rights/Uses ID, Inappropriate Data and Information, Power Outages, Server Down.Next, there are 30 possible risks that fall into the medium level of risk, namely dust and dirt, human error, unscheduled maintenance, new employees who do not really understand the system workflow, hacking, vandalism (damaging facilities such as computer equipment), lack of human resources as a whole. quality and quantity, System Error, Lightning, Cybercrime, Application user interface that is difficult to understand, Corrupt/Damaged Data, Overheat on computer devices, Network Failure, Web service suddenly shuts down, network system failure/network disconnection, Database Overload, Full Memory, Failure to back up data, damage or dysfunction to hardware, Virus Attack, CCTV not functioning properly, Generator not functioning properly, Backup Failure (backup failure), Failed to update, Device theft, Loss Data, Earthquakes, Fires, Hacking of networks. And there is 1 possible risk that falls into the low Level of Risk, namely flooding. Then Risk Prevention is carried out with the aim of reducing the risks that occur. This prevention activity is still considered profitable because it can provide a sense of security. Because it does not completely eliminate risk, it is still possible to reduce the percentage of risk occurring